Identification of the Irreversible Redox Behavior of Highly Fluorescent Benzothiadiazoles. Issue 9 (17th June 2020) - Rietsch, Philipp; Sobottka, Sebastian; Hoffmann, Katrin; Hildebrandt, Pascal; Sarkar, Biprajit; Resch‐Genger, Ute; Eigler, Siegfried
Abstract: Redox switches are applied in various fields of research, including molecular lifts, electronic devices and sensors. Switching the absorbance between UV and Vis/NIR by redox processes is of interest for applications in light harvesting or biomedicine. Here, we present a series of push‐pull benzothiadiazole derivatives with high fluorescence quantum yields in solution and in the crystalline solid state. Spectroelectrochemical analysis reveals the switching of UV‐absorption in the neutral state to Vis/NIR absorption in the reduced state. We identify the partial irreversibility of the switching process, which appears to be reversible on the cyclic voltammetry timescale. Abstract : Back and forth : A series of push‐pull benzothiadiazole derivatives with pronounced fluorosolvatochromism and high fluorescence quantum yields in solution and in the crystalline solid state is presented. Electrochemical reduction switches the absorption of the compounds from the UV region to the Vis/NIR region and back through oxidation. The spectroelectrochemical analysis reveals the partial irreversibility of the switching process, which appears to be reversible in the cyclic voltammogram.